Draft Twelfth Five Year Plan 2012-17 and Annual Plan 2012-13 Jammu and Kashmir - Planning Commission (Planning Commission, 2012)
The Eleventh Five Year Plan (2007-12) of Jammu & Kashmir had aimed at: (i)Acceleration of rate of growth to 8% by progressive increase in growth rate from 6.5% in the first year to 9% in the final year. It aimed at 4% per annum growth in primary sector, 7.5% in secondary sector and 10.5% in tertiary sector; (ii)Maximising employment generation - Creation of 5 lakh additional employment opportunities; (iii)Augmentation of power generation capacity by 505 MW;(iv) Electrification of all habitations; (v)Connecting all habitations with more than 500 inhabitants by road; and (vi)Provision of basic amenities (connectivity, power, water supply, primary health, and elementary education) to all villages.
Planning and Development Department, J and K Government